In vivo heat-stimulus-triggered osteogenesis. (19th December 2014) - Ikuta, Kunihiro; Urakawa, Hiroshi; Kozawa, Eiji; Hamada, Shunsuke; Ota, Takehiro; Kato, Ryuji; Honda, Hiroyuki; Kobayashi, Takeshi; Ishiguro, Naoki; Nishida, Yoshihiro
Abstract: Several studies have reported that heat stress stimulates the activity of osteoblastic cells in vitro . However, few have addressed the effects of heat stress on osteogenesis in vivo, nor have the optimal temperatures for bone formation been determined. The aim of the present study was to investigate the effects of hyperthermia treatment on osteogenesis in a rat tibial defect model. Forty-four Sprague Dawley rats were divided into two groups with or without hyperthermia treatment. A 3-mm circular defect in the proximal tibia filled with magnetite cationic liposomes embedded in alginate beads was subjected to hyperthermia treatment (43–46 °C). Radiological assessment at 2 weeks after the treatment showed that significantly stimulated osteogenesis was observed in the hyperthermia group as compared to the control group ( p = 0.003). Histomorphometrical analysis at 2 weeks revealed a significant increase of newly formed bone in the hyperthermia group, compared with the control group ( p < 0.001). Area of newly formed bone in each hyperthermia group was significantly increased as compared with the control group (43 °C; p = 0.005, 44 °C; p = 0.019, 45 °C; p = 0.003, and 46 °C; p = 0.003, respectively). Alkaline phosphatase was overexpressed at the surfaces of newly formed bone adjacent to magnetite cationic liposome implantation. Our results demonstrate for the first time that heat stimulus accelerates osteogenesis in vivo, and may thus be of interest as a novel and promising tool to induce osteogenesis clinically as well.